The Effect of Roasting Temperature at 400C and Sulphuric Acid Concentration on TiO2 Extraction Process from Zircon Sand Ilmenite - Eryuni Setyani; Tito Prastyo Rahman; Dwi Wahyu Nugroho; Sunardi Rahman; Fitria Irawan; Radyum Ikono; Nurul Taufiqu Rochman; Wipsar Sunu Brams Dwandaru (Jurnal Fisika dan Aplikasinya, 2014)
In this research, roasting temperature at 400C and sulphuric acid concentration variations was conducted to obtain titanium dioxide from zircon sand. The research was done through extraction metallurgy method which involved physical, chemical, and mechanical treatments. Zircon was magnetically separated, mixed with NaOH, and roasted with temperature of 400C. Characterization with XRD of the sample before and aftermagnetic separation was conducted. Peaks obtained from NaFeO2, NaTiO2, Na0.75Fe0.75Ti0.25O2, and TiO2 compounds were observed. In this study, the leaching process lasted in two stages. For the first leaching samples of combustion products are leached using distilled water to remove water-soluble impurities. For the second stage, the deposition obtained from stage one is leached using 8, 10, and 12 M concentrated sulphuric acid at high temperature to dissolve iron. XRD was used to characterize TiO2. The result showed that the sample at temperature of 400C and concentrated sulphuric acid of 12Mis whiter in colour compared to other samples. Furthermore, at temperature 400C and concentrated sulphuric acid of 12 M, the titanium dioxide produced is 32.3% and 11.5% for rutile and anatase, respectively.